(untitled) (Al-Academy, 2019)
For the purpose of achieving the desired goal of the educational learning process, it was necessary to devote attention to educational means and employ them in this field because of their great role in overcoming the difficulties facing the learning process and providing an educational environment that keeps abreast of the scientific developments. This is the goal of the research in which the researchers wanted to know the effect of the educational techniques in the development of apprentice students’ skills in teaching. The research consisted of the problem of the research which is: what is the impact of educational techniques on developing the apprentice students’ teaching skills in the Faculty of Fine Arts? In addition to its importance, objectives and hypotheses, and the definition of the terms in the title. The theoretical framework dealt with the educational techniques, their importance and their effective role in the educational process. The procedures used by the researchers included the methodology and the random sample which consisted of (40) students who were distributed equally into two controlling and experimental groups. The two researchers, after conducting the analysis, reached a set of results, the most important of which are the results that confirm the clear effect of the educational techniques on the students, and the researchers reached at the following conclusions:There are no differences in the assessment of teaching skills between the form approved by the college and the form used by the researchers. The educational techniques used by the researchers had the same effect in developing the teaching skills of the experimental group.